CHALLENGES OF INCLUSIVE GROWTH: BRIDGING ECONOMIC INEQUALITY IN CONTEMPORARY INDIA (International Journal of Food and Nutritional Sciences, 2022)
India's rapid economic growth has been accompanied by significant challenges related to economic inequality, posing obstacles to inclusive growth. This paper examines the multifaceted nature of economic inequality in contemporary India, focusing on income and wealth disparities, access to quality education, and social services. It identifies key challenges hindering inclusive growth, including the urban-rural divide, caste-based disparities, and gender inequalities. The study employs a mixed-methods approach, utilizing both quantitative and qualitative data to analyze trends in inequality and evaluate the effectiveness of existing government policies aimed at promoting inclusivity. Key government initiatives such as the Mahatma Gandhi National Rural Employment Guarantee Act (MGNREGA), Pradhan Mantri Jan Dhan Yojana (PMJDY), and the Skill India Mission are critically assessed to understand their impact on bridging economic gaps. While these programs have made notable contributions, significant gaps and inefficiencies remain in their implementation, limiting their effectiveness in addressing the root causes of inequality. The paper concludes with actionable policy recommendations, emphasizing the need for enhanced access to quality education, greater financial inclusion, and targeted support for marginalized communities. By leveraging technology and fostering public-private partnerships, India can create a more equitable economic landscape. This study highlights the urgent need for a cohesive strategy that not only promotes economic growth but also ensures that all segments of society benefit from it, ultimately fostering a more just and inclusive India.